(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
In this study, we examine the effect of incident sea spectrum width and shape on the performance of a top-hinged wave energy converter (WEC). We look at two performance indicators: (i) spectrum power and (ii) spectrum velocity, to examine power over moment. We look at two idealised symmetric spectra, Tophat and Gaussian, and a realistic spectrum, Bretschneider. We find that for the symmetric spectra, spectrum power and spectrum velocity decrease for wider spectra, and this decrease is more significant for the Gaussian spectra than the Tophat spectra. We also find that the optimal value of resonant wavenumber to maximise power decreases with spectrum width, whereas the optimal value of resonant wavenumber to maximise spectrum velocity increases with spectrum width. This suggests differing conclusions for the size of a WEC from the two performance indicators: (i) to maximise spectrum power, the WEC should be larger for a wider incident spectra, but (ii) to maximise spectrum velocity, the WEC should be smaller for a wider incident spectrum. In comparison to the idealised spectra, the Bretschneider spectrum results in a smaller spectrum power but a larger spectrum velocity, due to a smaller low-frequency tail and larger high-frequency tail. The novel shape considered in this study was originally discovered using a geometry optimisation considering a monochromatic wave, so the present study is a first step at generalising the analysis to more realistic conditions.